Faktor - Faktor yang Mempengaruhi Kepatuhan Wajib Pajak UMKM dalam Melaksanakan Kewajiban Perpajakan: Studi Kasus pada Wajib Pajak UMKM di KPP Pratama Seberang Ulu - Adilla, Nur Atika; Ade Kemala Jaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to examine the effect of tax knowledge, tax sanctions, service quality, tax rates and application of e-filing on taxpayer compliance of UMKMs at KPP Pratama Seberang Ulu. The independent variables in this study are tax knowledge, tax sanctions, service quality, tax rates and application of e-filing while the dependent variable is taxpayer compliance. There are 2 theories in this study, namely attribution and the theory of Planned Behavior. This study uses a quantitative method. The population in this study are UMKM actors registered at KPP Pratama Seberang Ulu. The sample was determined using purposive sampling. Data were collected by distributing questionnaires to 47 UMKMs registered at KPP Pratama Seberang Ulu and in accordance with the specified characteristics. Primary data collection techniques and data analysis using multiple linear regression analysis SPSS software version 25. The methods used in this study are Descriptive Analysis, Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis Test, F Test, R2 Determination Coefficient Test and t Test. The results of the study indicate that tax knowledge, tax sanctions and the application of e-filing have an effect on taxpayer compliance, while the quality of service and tax rates have no effect on the compliance of UMKM taxpayers at the Seberang Ulu Pratama Tax Office..